Agile Development Methods Dalam Perancangan Aplikasi Penjualan Berbasis E-Commerce Pada Pt.Indo Gemilang Sakti - Muhammad Hafiz bm; Titis Wicaksosno; Elsa Apriliani; Wasis Haryono (BULLET : Jurnal Multidisiplin Ilmu, 2022)
With E-Commerce-Based sales services, all services performed by customers can be processed immediately, so that the company will be able to provide the best and fast service. The problem in buying and selling activities carried out by PT.INDO GEMILANG SAKTI at this time is that sales have not been carried out online (online). Therefore, the author wants to make an online sales system that is used as a place to promote goods that will be sold on the system. Agile method is a software development that requires relatively fast time and does not require large resources. By using the Agile Method, the author will build a software (software) online sales system based on E-Commerce which is used at PT.INDO GEMILANG SAKTI. This system has the convenience of marketing and selling company-owned products with the process of buying and selling products, namely payments using mobile banking without having to go to a store. With the E-Commerce-Based Application that utilizes the internet as a marketing medium, it can make it easier for shop owners to provide services to consumers/customers optimally and provide 24-hour information and can be accessed anywhere and anytime. Keywords – pt. indo gemilang sakti; e-commerce; agile methods.